Fine-Tuning YOLOv11 Architecture for Real-Time Object Detection on Mobile Devices for Visually Impaired - Arsya Prima Al Azmi; Muhammad Fachrie (Komunitas Dosen Indonesia, 2025)
Visual impairment presents significant challenges in daily navigation and environmental interaction, impacting personal independence and safety. This research addresses these challenges by developing